2019
DOI: 10.1158/0008-5472.can-18-3210
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA ELIT-1 Acts as a Smad3 Cofactor to Facilitate TGFβ/Smad Signaling and Promote Epithelial–Mesenchymal Transition

Abstract: Nucleus Cytoplasm TGF Smad3 P Smad4 ELIT-1 Positive feedback loop Snail, Vimentin, PAI-1 etc

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 61 publications
0
62
0
Order By: Relevance
“…TGF-β is a multifunctional regulatory protein that can regulate multiple cellular processes, and is known to be particularly important in tumor metastasis [ 9 , 10 ]. It promotes tumor progression by facilitating the invasion of various types of tumor cells via EMT [ 11 , 12 ]. The underlying regulatory mechanisms of TGF-β-induced EMT in NPC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β is a multifunctional regulatory protein that can regulate multiple cellular processes, and is known to be particularly important in tumor metastasis [ 9 , 10 ]. It promotes tumor progression by facilitating the invasion of various types of tumor cells via EMT [ 11 , 12 ]. The underlying regulatory mechanisms of TGF-β-induced EMT in NPC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that lncRNAs play a crucial role in human diseases, especially in various cancers. [17][18][19][20][21][22][23][24][25][26][27][28] LncRNAs participate in almost all cellular sh-TP-53, sh-ESR1, and sh-NC. D, DDX3 and YY1 coimmunoprecipitation and western blot assay were conducted in DLD-1 cells, which transfected the overexpression of TCONS_00012883 and controls.…”
Section: Discussionmentioning
confidence: 99%
“…19 LncRNA ELIT-1 facilitates TGF-β/Smad signaling through interacting with Smad3. 20 Although researches on lncRNAs have progressed rapidly, the functions of most lncRNAs are still unclear. Therefore, it is essential to explore the functions of lncRNAs in CRC progression.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that down-regulation of LTBP1 was accompanied by decreased expression of TGFβ, N-cadherin and vimentin, as well as increased expression of E-cadherin in ESCC cells, suggesting that LTBP1 may involve in regulating the secretion and activation of TGFβ and play an important role in promoting EMT in ESCC cells. TGFβ is the most well-known stimulator of EMT and metastasis in cancer [28,29], so we treated ESCC cells with TGFβ in our study. The results showed that LTBP1 altered the expression of proteins associated with TGFβ-induced EMT.…”
Section: Discussionmentioning
confidence: 99%